A Review of Structural Equation Model for Construction Delay Study - Ramli, Mohd Zakwan; Malek, Marlinda Abdul; Muda, Mohamad Zaki; Talib, Zulkhairi Abd; Azman, Nor Syahirah; Fu’ad, Nur Farah Syazana Mohamad; Zawawi, Mohd Hafiz; Katman, Herda Yati (International Journal of Engineering and Technology, 2018)
Structural Equation Modelling (SEM) has been widely used in science social area compared to construction engineering and management field especially in area of delay construction. SEM is a second generation multivariate analysis that has an advance features compare to first generations of analysis tools. First generation techniques suffer with some assumptions such as error measurement is neglected, only observed variable allowed, only for simple model and other limitations. In construction delay study, comprehensive and complex analysis which involves hidden variables need to be considered to get precise results. Therefore, the main objective of this paper is to review the importance of applying SEM for construction delay study. Various papers which were taken from construction delay and construction management studies has been reviewed to observe the suitability of SEM for construction delay study. Outcome of this review reveals that SEM can include latent variable in the analysis model and consider of error measurement as integral part of the model as well as simultaneously analyse theory and measurement in a structural model while it is unobtainable for first generation techniques.Â This review proves that SEM can be an appropriate analysis tool for construction delay study.